2010
DOI: 10.1097/01.aids.0000386736.25296.8d
|View full text |Cite
|
Sign up to set email alerts
|

HIV, hepatitis B, and hepatitis C prevalence and associated risk behaviors among female sex workers in three Afghan cities

Abstract: Objective To assess prevalence of HIV, syphilis, and hepatitis B (HBV) and C virus and associated risk behaviors among female sex workers (FSWs) in three Afghan cities. Design: Cross-sectional prevalence assessment. Methods Consented FSWs from Jalalabad, Kabul, and Mazar-i-Sharif completed an interviewer-administered questionnaire, pre and post-test counseling, and rapid and confirmatory testing for HIV, HCV, HBV and syphilis. Logistic regression was used to detect correlates associated with HBV infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 23 publications
8
51
2
3
Order By: Relevance
“…These characteristics seem common among female sex workers in Brazil and in other countries (9,(18)(19)(20)(21)(22) . In this study, as well as in others conducted with difficult to reach populations, adherence to the first dose was good, demonstrating this population's willingness for vaccination (9)(10)23) .…”
Section: Discussionmentioning
confidence: 92%
“…These characteristics seem common among female sex workers in Brazil and in other countries (9,(18)(19)(20)(21)(22) . In this study, as well as in others conducted with difficult to reach populations, adherence to the first dose was good, demonstrating this population's willingness for vaccination (9)(10)23) .…”
Section: Discussionmentioning
confidence: 92%
“…Sex with a customer is often accompanied by alcohol consumption, as shown by studies in Afghanistan (Todd et al, 2010), China (Rogers et al, 2002;Wang et al, 2010), India (Bowen et al, 2010;Go et al, 2010;Samet et al, 2010;Verma et al, 2010), Kenya (Chersich et al, 2007), Mongolia (Witte et al, 2010), the Philippines (Chiao et al, 2006;Morisky et al, 2010), Scotland (Thomas et al, 1990), South Africa (Wechsberg et al, 2005;Wechsberg et al, 2009), Tanzania Fisher et al, 2010), the United States (Nemoto et al, 2003), and Vietnam (Nemoto et al, 2008). Alcohol is also consumed by male clients of FSWs in India (Madhivanan et al, 2005;Rodríguez et al, 2010;Samet et al, 2010;Schensul et al, 2010;Verma et al, 2010), Scotland (Morgan Thomas et al, 1990), Sri Lanka (Dissabandara et al, 2009), Thailand (Havanon et al, 1993), and Zimbabwe (Fritz et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Other reasons for alcohol use were to conform to norms of sex partners who preferred them to be intoxicated and would pay more in these situations (Witte et al, 2010). Other groups also report than some FSWs use alcohol to make sex easier (Wechsberg et al, 2005;Nemoto et al, 2008;Todd et al, 2010). Drinking before sex with a client is linked with life-long inconsistent condom use in 454 FSWs (Wang et al, 2010).…”
Section: Female Sex Workersmentioning
confidence: 99%
“…In another study of female sex workers the prevalence of HIV was 0.19%, HCV was 1.92%, and HBV was 6.54. HBV was associated age, ever using alcohol, anal sex and having children [18]. In a cross-sectional sample of adult injection drug users (IDUs) in Kabul, Afghanistan it was reported that the overall prevalence of HIV, HCV, and HBsAg were 3.0%, 36.6% and 6.5% respectively.…”
Section: Introductionmentioning
confidence: 99%